2020
DOI: 10.1111/cas.14312
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal simvastatin sensitizes C26 murine colon carcinoma to the antitumor effects of liposomal 5‐fluorouracil in vivo

Abstract: 5-Fluorouracil-based therapy remains the main approach in colorectal cancer, even though there are still some drawbacks, such as chemoresistance. In this study we combined 5-fluorouracil encapsulated in long-circulating liposomes with simvastatin, also encapsulated in long-circulating liposomes, that was previously proved to exert antitumor actions on the same tumor model. The production of angiogenic/inflammatory proteins was assessed by protein array and the production of markers for tumor aggressiveness (Bc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Similarly, as the main therapeutic strategy for colorectal cancer, 5-FU-based treatment options have some shortcomings, including the risk of chemotherapy resistance. Recent evidence suggests that simvastatin may enhance the sensitivity of C26 mouse colon cancer cells to 5-FU treatment [ 301 ]. Pereira et al found that statins temporarily modulated the epidermal growth factor receptor (EGFR) and prostate specific membrane antigen (PSMA) on the surface of tumor cells, which enhanced the tumor-binding avidity of the monoclonal antibodies panitumumab, cetuximab and huJ591, thereby synergizing with the antitumor effects of these agents [ 302 ].…”
Section: Maximizing Efficacy and Addressing Shortcomings Of Conventional Cancer Therapymentioning
confidence: 99%
“…Similarly, as the main therapeutic strategy for colorectal cancer, 5-FU-based treatment options have some shortcomings, including the risk of chemotherapy resistance. Recent evidence suggests that simvastatin may enhance the sensitivity of C26 mouse colon cancer cells to 5-FU treatment [ 301 ]. Pereira et al found that statins temporarily modulated the epidermal growth factor receptor (EGFR) and prostate specific membrane antigen (PSMA) on the surface of tumor cells, which enhanced the tumor-binding avidity of the monoclonal antibodies panitumumab, cetuximab and huJ591, thereby synergizing with the antitumor effects of these agents [ 302 ].…”
Section: Maximizing Efficacy and Addressing Shortcomings Of Conventional Cancer Therapymentioning
confidence: 99%
“…Moreover, the co-culture between melanoma cells and IL-13-LCL-SIM-treated M2 macrophages rendered B16.F10 melanoma cells more susceptible to the antiproliferative effects of PEG-EV-DOX ( Figure 2B ), which was also confirmed by the 2-fold decrease in the IC 50 of PEG-EV-DOX-treated B16.F10 proliferation in the presence of IL-13-LCL-SIM treated TAMs ( Table 3 ). Based on these results and on previous studies in which we demonstrated that liposomal SIM can sensitize cancer cells to cytotoxic agents ( Luput et al, 2020 ) or that intrinsic DOX resistance in melanoma can be overcome by simultaneous administration of inhibitors of TAM pro-tumor functions ( Licarete et al, 2020 ), we administered the novel combination therapy in vivo , sequentially as detailed in Supplementary Figure S1 . Our data clearly showed that among the monotherapies, IL-13-conjugated LCL-SIM and PEG-EV-DOX elicited the strongest reduction in tumor volume ( Figures 3A,B ).…”
Section: Discussionmentioning
confidence: 89%
“…Co-treatment of Simva and flavons decreases chemo-resistance to doxorubicine via degradation of multi drug resistance (MDR) proteins in human colon cancer cells [80]. In another investigation, it has been showed that liposomal Simva sensitizes C26 colon carcinoma cells to liposomal 5-FU via inhibition of tumor angiogenesis in vivo [81]. Simvastatin also sensitizes A549 non-small cell lung cancer to Sulindac, or Pemetrexed (multi-target antifolate medication) induced caspase-dependent apoptosis via damaging mitochondria and increasing ROS [82,83].…”
Section: Discussionmentioning
confidence: 99%